Beyond borders, beyond boundaries: How globalization affects real estate prices - MEHLAWAT, Ritu (Institutional Knowledge at Singapore Management University, 2024)
In this comprehensive study, we aim to investigate the impact of Globalisation on house prices globally. Our analysis spans annual data from 42 countries, including OECD and some Non-OECD countries, from 1991 to 2021. Our research underscores the role of Globalisation in shaping house prices, with distinct impacts contingent on the type of Globalisation. Financial globalisation, which primarily encompasses capital flow coupled with enabling regulatory environment, is one of the drivers of house price increases. Conversely, Interpersonal, and Informational globalisation, which mainly involves the physical or virtual proximity of people supported by favourable conditions, has a negative effect on house prices in higher income countries (OECD countries) and positive effect on house prices in lower income countries. Our results suggest that Globalisation is a double-edged sword when it comes to house prices, a conclusion that economists, investors and policymakers can use in their decision making.